Better common than rare? Effects of low reproductive success, scarce pollinator visits and interspecific gene flow in threatened and common species of Tibouchina (Melastomataceae). Issue 4 (30th October 2015) - Ruilova, Xavier Rojas; Marques, Isabel
Abstract: The reasons for plant rarity have been the focus of many studies, especially because rare species are more prone to extinction than common species. Under the same habitat conditions, rare plants are expected to attract fewer flower visitors and to show some limitation in their reproductive success. Here, using one of the most emblematic Neotropical plant genus ( T ibouchina ) we tested whether narrow endemic and threatened species in Ecuador have a lower reproductive success or are visited by fewer pollinators than common species, in 13 populations monitored from 2011 to 2013. We also assessed whether interspecific gene flow could be considered a threat to the rare species. However, contrary to expectations, we found that few pollinators visited the flowers, independently of species rarity. Natural outcross pollinations were always very low in all small‐size populations, leading to high levels of pollen limitation. Interspecific crossing experiments also revealed weak reproductive barriers in some species. This study reveals that both narrow and common species of T ibouchina have similar reproductive and pollinator patterns in Ecuador and, therefore, other causes of the rarity of these species should be considered. Abstract : Using one of the most emblematic Neotropical plant genus ( Tibouchina ) we tested whether narrow endemics and threatened species in Ecuador have a lower reproductive success or are visited by fewer pollinators than common species, in 13 populations monitored from 2011 to 2013. However, contrary to expectations, we found that both narrow and common species of Tibouchina have similar reproductive and pollinator patterns in Ecuador. Further, interspecific gene flow could be considered a threat to the rare species.